MAKNA TOPIK ‘WARISAN’ DALAM UNGGAHAN FACEBOOK AFI NIHAYA FARADISA: ANALSIS WACANA KRITIS - Kusno, Ali; Rusbiyantoro, Wenni (Kantor Bahasa Provinsi Gorontalo, 2017)
Afi N.F., a student of SMA Negeri 1 Gambiran Bayuwangi had been stolenthe attention of the Indonesian people in May 2017. Afi N.F. upload an article on Facebook titled 'Warisan' is getting massive attention from the community and at the same time triggered the debates among social media users. This study aimed to express the meaning contained in the article. This research used critical discourse analysis of Fairclough Model. The research data was taken from the triggered titled “Warisan”. Data analysis technique using an interactive model. The results showed a significant message to all the Indonesian nation to maintain tolerance, especially in social media that is prone to friction among its users. In the article, Afi had been highlighting the issues of identity, such as religion, ethnicity, race, and nationality are inherited from parents, as she stated in her writing. Afi also invites all the people of Indonesia to live the Pancasila, the 1945 Constitution, and also the motto of Bhinneka Tunggal Ika so the life of religious tolerance will be maintained.